ANALISIS KEBUTUHAN LULUSAN PROGRAM STUDI (PRODI) TELEKOMUNIKASI DAN NAVIGASI UDARA (TNU) SEKOLAH TINGGI PENERBANGAN INDONESIA (STPI) DI PERUSAHAAN UMUM LEMBAGA PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA (LPPNPI) TANGERANG – BANTEN - Pribadi Asih (Politeknik Penerbangan Indonesia Curug, 2020)
Needs analysis study on Telecommunication and Air Navigation STPI Graduates at Perusahaan Umum Lembaga Penyelenggara Pelayanan Navigasi Penerbangan Indonesia (LPPNPI) Tangerang – Banten. This analyses is applied to get the information for about whether the graduate of TNU is still needed, How much is needed, is there any constraint in absorbing the needs of the graduates. To achieve these objectives used descriptive research methods Analysis and Observation in the field. In this research, where the research describes the situation which is accompanied by a clear analysis of human resources graduates on the STPI TNU study program in Perum LPPNPI / Airnav Indonesia Tangerang with the data and problems that exist, by giving conclusions and suggestions.